The influence of accounting computer information processing technology on enterprise internal control under panel data simultaneous equation - Shan, Rui; Xiao, Xianfei; Dong, Guangming; Zhang, Zhaoyong; Wen, Qian; Ali, Basel (Applied mathematics and nonlinear sciences, 2023)
In order to explore the effect of accounting computer information processing technology on enterprise internal control, this paper puts forward the method of simultaneous equation of panel data. This paper constructs an accounting computer index to measure the accounting computer level of manufacturing enterprises in Shanghai stock market, and studies the relationship between enterprise accounting computer and internal control by using panel data simultaneous equations model. The empirical results show that: first, although the average accounting computer level of manufacturing industry increases year by year, the overall level is low, and there are great differences among sub industries, even within the same industry; Second, the level of accounting computer has a negative impact on the internal control of enterprises, and the internal control of enterprises has a positive impact on the level of accounting computer; Third, enterprise scale and operating years have a significant positive impact on the level of accounting computer. The experimental results show that: from the estimation results of accounting computer equation, firstly, ROA has a significant positive impact on the level of accounting computer; Secondly, the scale and operating age of enterprises positively affect the level of accounting computer, while the nature of ownership and listing age are not related to the level of accounting computer; Finally, document disclosure has a high level of accounting computer, which is consistent with the conclusion of the above descriptive statistics of EMI, which may be related to the mandatory provisions of national laws and regulations on the industry of document disclosure.